2001
DOI: 10.1046/j.1468-3083.2001.00148.x
|View full text |Cite
|
Sign up to set email alerts
|

Familial erythromelanosis follicularis and chromosomal instability

Abstract: We report a 17-year-old male patient with erythromelanosis follicularis faciei et colli (EFFC), oral leucokeratosis and diabetes mellitus without islet cell antibody. His sister also had minimal findings of EFFC and minimal follicular papules on her shoulders and extensor surfaces of the arms. The father had only fine follicular papules, but no erythromelanosis. Skin and mucous membrane lesions of the proband were investigated histopathologically. Interestingly, in peripheral lymphocyte cultures of the family … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 12 publications
(12 reference statements)
0
14
0
Order By: Relevance
“…Tuzun et al. 11 suggested that EFFC may be a polyaetiological disorder (i.e. familial and environmental) and might be considered one of the chromosomal instability syndromes.…”
Section: Reportmentioning
confidence: 99%
“…Tuzun et al. 11 suggested that EFFC may be a polyaetiological disorder (i.e. familial and environmental) and might be considered one of the chromosomal instability syndromes.…”
Section: Reportmentioning
confidence: 99%
“…Erythromelanosis follicularis faciei et colli is a rare disease of unknown etiology, but an autosomal recessive pattern of inheritance and familial cases [2][3][4][5], and spontaneous mutation and chromosomal instability have been reported in some cases [5,6]. This condition was initially reported in young male patients, but a recent study showed nearly equal incidence between males and females [4].…”
Section: Discussionmentioning
confidence: 99%
“…1 A few more cases have been reported from different parts of the world, but the total number of reported cases worldwide is only about a hundred. 1,19 The clinical appearance consisted of sharply demarcated patches of erythema, hyperpigmentation and follicular plugging with or without telangiectasia. 1,19 The cheeks and periauricular area were commonly involved with extension of lesions to the side of neck.…”
Section: Discussionmentioning
confidence: 99%
“…1,19 The clinical appearance consisted of sharply demarcated patches of erythema, hyperpigmentation and follicular plugging with or without telangiectasia. 1,19 The cheeks and periauricular area were commonly involved with extension of lesions to the side of neck. Involvement of the auricle and eyebrows has been regarded as unique and atypical 9,10 but in a recent report from Iran, it was common.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation